Long-term kidney outcomes of semaglutide in obesity and cardiovascular disease in the SELECT trial - Colhoun, Helen M.; Lingvay, Ildiko; Brown, Paul M.; Deanfield, John; Brown-Frandsen, Kirstine; Kahn, Steven E.; Plutzky, Jorge; Node, Koichi; Parkhomenko, Alexander; Rydén, Lars; Wilding, John P.H.; Mann, Johannes; et al. (Nature Medicine, 2024)
The SELECT trial previously reported a 20% reduction in major adverse cardiovascular events with semaglutide (n = 8,803) versus placebo (n = 8,801) in patients with overweight/obesity and established cardiovascular disease, without diabetes. In the present study, we examined the effect of once-weekly semaglutide 2.4 mg on kidney outcomes in the SELECT trial. The incidence of the pre-specified main composite kidney endpoint (death from kidney disease, initiation of chronic kidney replacement therapy, onset of persistent estimated glomerular filtration rate (eGFR) < 15 ml min−1 1.73 m−2, persistent ≥50% reduction in eGFR or onset of persistent macroalbuminuria) was lower with semaglutide (1.8%) versus placebo (2.2%): hazard ratio (HR) = 0.78; 95% confidence interval (CI) 0.63, 0.96; P = 0.02. The treatment benefit at 104 weeks for eGFR was 0.75 ml min−1 1.73 m−2 (95% CI 0.43, 1.06; P < 0.001) overall and 2.19 ml min−1 1.73 m−2 (95% CI 1.00, 3.38; P < 0.001) in patients with baseline eGFR <60 ml min−1 1.73 m−2. These results suggest a benefit of semaglutide on kidney outcomes in individuals with overweight/obesity, without diabetes. ClinicalTrials.gov identifier: NCT03574597.
CRIS-Team Scopus Importer:2024-06-07